Optimal design and biomechanical analysis of sandwich composite metal locking screws for far cortical locking constructs - Deng, Yuping; Zhao, Dongliang; Yang, Yang; Ouyang, Hanbin; Xu, Chujiang; Xiong, Liang; Li, Yanbin; Tan, Wenchang; Huang, Gang; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2022)
In the interests of more flexible and less stiff bridge constructs to stimulate bone healing, the technique of far cortical locking has been designed to improve locked plating constructs in terms of stress concentration, stress shielding, and inhibition of issues around fracture healing. However, far cortical locking screws currently lack objective designs and anti-fatigue designs. This study investigates an optimization algorithm to form a special locking screw composed of various metals, which can theoretically achieve the maintenance of the excellent mechanical properties of far cortical locking constructs in terms of fracture internal fixation, while maintaining the biomechanical safety and fatigue resistance of the structure. The numerical results of our study indicate that the maximum von Mises stress of the optimized construct is less than the allowable stress of the material under each working condition while still achieving sufficient parallel interfragmentary motion. Numerical analysis of high cycle fatigue indicates that the optimized construct increases the safety factor to five. A high cycle fatigue test and defect analysis indicates that the sandwich locking constructs have better fatigue resistance. We conclude that the sandwich locking construct theoretically maintains its biomechanical safety and fatigue resistance while also maintaining excellent mechanical properties for fracture internal fixation.